2017
DOI: 10.1007/s11145-017-9736-2
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking listening comprehension: the role of vocabulary, morphological awareness, and syntactic knowledge in reading comprehension

Abstract: As posited by the simple view of reading, listening comprehension and decoding are necessary for reading comprehension. Thus, the present study examined subcomponents of listening comprehension (i.e., vocabulary, morphology, and syntax) and their contributions to reading comprehension. The novel aspect of this study is that rather than examining listening comprehension as a global variable, the unique and shared variance of subcomponents of listening comprehension were examined in relation to English reading c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 72 publications
(123 reference statements)
4
57
0
8
Order By: Relevance
“…The overall correlation effect size was nearly large. The result is consistent with previous survey studies that have shown that vocabulary knowledge had great variance in explaining the mental image construction process via verbal cognition and semantic identification (Cain et al, 2004 ; Quinn et al, 2015 ; Gottardo et al, 2018 ). For example, vocabulary knowledge provides different potential semantic meanings of the target word or characters to assist readers' cognition of the adjacent coherence between words and sentences (Prior et al, 2014 ; Perfetti, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…The overall correlation effect size was nearly large. The result is consistent with previous survey studies that have shown that vocabulary knowledge had great variance in explaining the mental image construction process via verbal cognition and semantic identification (Cain et al, 2004 ; Quinn et al, 2015 ; Gottardo et al, 2018 ). For example, vocabulary knowledge provides different potential semantic meanings of the target word or characters to assist readers' cognition of the adjacent coherence between words and sentences (Prior et al, 2014 ; Perfetti, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, the simple view of reading does not provide a detailed account of which component skills underpin listening comprehension or underlie its relation to reading comprehension. The current research evidence highlights the importance of an augmented simple view of reading, which takes into account specific component skills of comprehension for a better understanding of both listening and reading comprehension processes such as reading fluency, working memory, morphological and syntactic skill (Farnia & Geva, 2013;Geva & Farnia, 2012;Gottardo, Mirza, Koh, Ferreira, & Javier, 2018;Hogan, Adlof, & Alonzo, 2014;Lervåg, Hulme, & Melby-Lervåg, 2017;Perfetti, Landi, & Oakhill, 2005). Among these vocabulary knowledge and grammar (including morphological and syntactic skills) are fundamental for processing of the meaning of sentences and formation of a mental representation of written text and have been specifically associated with reading comprehension skills (Adlof et al, 2006;Gottardo et al, 2018;NICHD, 2005).…”
Section: Oral Language Skills That Underpin Listening and Reading Commentioning
confidence: 92%
“…However, rarely do studies examine the role of these skills in both listening and reading comprehension. Instead, there is a tendency to focus on vocabulary as a proxy measure of listening comprehension, which makes it difficult to evaluate the extent to which the core oral language skills (i.e., vocabulary and grammar) underlie the relations between listening and reading comprehension and the nature of these relations (for a detailed discussion, see Gottardo et al, 2018). Therefore, it is not clear whether the role of vocabulary and grammar in reading comprehension should be understood as being direct or largely indirect through their influence on listening comprehension.…”
Section: Oral Language Skills That Underpin Listening and Reading Commentioning
confidence: 99%
See 1 more Smart Citation
“…The development of listening and reading comprehension in a second language (L2) differs from the development in the mother tongue (L1), where auditory comprehension skills are naturally acquired in early childhood and the acquisition of reading skills usually originates in elementary school. Still, theories like the simple view of reading explain (early) reading comprehension in L1 and L2 as a product of decoding and listening comprehension; a larger number of studies provided evidence for the theory in L2 learning (e.g., Yagoub-Zadeh et al, 2012;Gottardo et al, 2018). On the other hand, L2 listening comprehension, especially in early stages of L2 learning, involves different tasks for the language learner and requires high levels of attention and working memory, as the speed and pronunciation of an authentically spoken foreign language is hardly controllable by the listener (e.g., Vandergrift, 2007;Vandergrift and Baker, 2015).…”
Section: Theoretical Background Listening and Reading Comprehension Amentioning
confidence: 99%